2009
DOI: 10.1021/bi901078y
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Molecular Modeling and Biophysical Characterization of Manduca sexta Eclosion Hormone

Abstract: Eclosion hormone (EH) is an integral component in the cascade regulating the behaviors culminating in insect emergence from the old exoskeleton. Little is known regarding the EH solution structure, consequently, we utilized a computational approach to generate a hypothetical structure for Manduca sexta EH. The de novo algorithm exploited the restricted conformational space of disulfide bonds (Cys14-Cys38, Cys18-Cys34, and Cys21-Cys49) and predicted secondary structure elements to generate a thermodynamically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In our study, the Mro-EH transcript was discovered in both the eyestalk and CNS transcriptomes. Based on multiple sequence alignment, the Mro-EH mature peptide displays six conserved cysteine residues that may be responsible for the formation of three-disulfide bridges [ 81 , 82 ]. RT-PCR showed that the Mro-EH gene was expressed in the brain and thoracic ganglia, but not in the other tissues, including the eyestalk, probably due to low or no expression.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the Mro-EH transcript was discovered in both the eyestalk and CNS transcriptomes. Based on multiple sequence alignment, the Mro-EH mature peptide displays six conserved cysteine residues that may be responsible for the formation of three-disulfide bridges [ 81 , 82 ]. RT-PCR showed that the Mro-EH gene was expressed in the brain and thoracic ganglia, but not in the other tissues, including the eyestalk, probably due to low or no expression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an alignment of EH sequences from various insects shows that the Nasonia EH contains only two of the three disulfide bridges usually present in EHs ( Figure 6). 42,43 ETH. In insects, ecdysis triggering hormone (ETH) is expressed in Inka cells and initiates molting.…”
Section: Figurementioning
confidence: 99%
“…Even the initiation of the molting process has started, there is no guarantee that the animal will molt successfully as the fulfillment of the subsequent events must be straightly followed. In insects, neuropeptides that induce molting behavior include ecdysis-triggering hormone (ETH) (Shi et al, 2019a;Minh Nhut et al, 2020;Shen et al, 2021), eclosion hormone (EH) (Hull et al, 2009;Zhou et al, 2017;Scott et al, 2020), crustacean cardioactive peptide (CCAP) (Veelaert et al, 1997;Arakane et al, 2008;Jackson et al, 2009), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Eclosion hormones (EH) is a neuropeptide that influences several aspects of pupal-adult ecdysis as well as larval-larval ecdysis (Hull et al, 2009;Scott et al, 2020). It was first characterized in the moth Bombyx mori as a brain neuropeptide (Truman and Riddiford, 1970).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation